Carta de Federico Henríquez y Carvajal a Roberto H. Todd - Henríquez y Carvajal, Federico; Todd, Roberto H. (My University, 1938)
Carta relacionada a la bandera de Puerto Rico y a las dolencias de Henríquez.
Keywords: Flags--Puerto Rico.; Bandera--Puerto Rico.